Zotarolimus-Eluting Versus Bare-Metal Stents in Uncertain Drug-Eluting Stent Candidates - Valgimigli Marco; Patialiakas Athanasios; Thury Attila; McFadden Eugene; Colangelo Salvatore; Campo Gianluca; Tebaldi Matteo; Ungi Imre; Tondi Stefano; Roffi Marco; Menozzi Alberto; Cesare Nicoletta de; et al. (2015)
BACKGROUND The use of drug-eluting stents (DES) in patients at high risk of bleeding or thrombosis has not been prospectively studied; limited data are available in patients who have a low restenosis risk. OBJECTIVES This study sought to compare a hydrophilic polymer-based, second-generation zotarolimus-eluting stent (ZES) with a unique drug fast-release profile versus bare-metal stents (BMS) under similar durations of dual-antiplatelet therapy (DAPT). METHODS We randomly assigned 1,606 patients with stable or unstable symptoms, and who on the basis of thrombotic bleeding or restenosis risk criteria, qualified as uncertain candidates for DES, to receive ZES or BMS. DAPT duration was on the basis of patient characteristics, rather than stent characteristics, and allowed for a personalized 1-month dual antiplatelet regimen. The primary endpoint was the risk of 1-year major adverse cardiovascular events (MACE), which included death, myocardial infarction (MI), or target vessel revascularization (TVR). RESULTS Median DAPT duration was 32 days (interquartile range [IQR]: 30 to 180 days) and did not differ between the groups. In the ZES group, 140 patients (17.5%) reached the primary endpoint, compared with 178 patients (22.1%) in the BMS group (hazard ratio: 0.76; 95% confidence interval: 0.61 to 0.95; p = 0.011) as a result of lower MI (2.9% vs. 8.1%; p < 0.001) and TVR rates (5.9% vs. 10.7%; p = 0.001) in the ZES group. Definite or probable stent thrombosis was also significantly reduced in ZES recipients (2.0% vs. 4.1%; p = 0.019). CONCLUSIONS Compared with BMS, DES implantation using a stent with a biocompatible polymer and fast drug-eluting characteristics, combined with an abbreviated, tailored DAPT regimen, resulted in a lower risk of 1-year MACE in uncertain candidates for DES implantation. (Zotarolimus-eluting Endeavor Sprint Stent in Uncertain DES Candidates [ZEUS] Study; NCT01385319) (C) 2015 by the American College of Cardiology Foundation.
Keywords: Klinikai orvostan